ENSURING NATIONAL SECURITY IN INDIA: CONTEMPORARY CHALLENGES AND LEGAL INSIGHTS (International Journal of Food and Nutritional Sciences, 2022)
National security is a paramount concern for India, a diverse and rapidly evolving nation. This study, titled "Ensuring National Security in India: Contemporary Challenges and Legal Insights," delves into the multifaceted dimensions of India's national security landscape, addressing the complex challenges it faces in the 21st century. In this research, we explore the contemporary security challenges confronting India, encompassing traditional threats such as border disputes and terrorism, as well as emerging challenges in cyberspace, economic espionage, and disinformation campaigns. The study sheds light on the evolving nature of these threats, their implications for India's stability, and the need for adaptive responses. The legal dimension is a crucial aspect of ensuring national security while upholding democratic values and individual rights. We examine India's legal frameworks, including counterterrorism laws, cybersecurity regulations, and data protection measures, evaluating their effectiveness and their role in addressing modern security challenges. Striking a balance between safeguarding national security and protecting civil liberties is a central theme in this analysis. the study explores India's engagement with international law and cooperation mechanisms, emphasizing its role in addressing global security issues. India's participation in international organizations and its approach to multilateral agreements are considered, highlighting the interconnectedness of security challenges in the contemporary world.